Modelling sustainability maturity in corporate real estate management. Issue 2 (2014) - ,; ,; ,; ,
Abstract : Purpose – Sustainability in corporate real estate management (CREM) has been lately recognized as an integral part of almost every business. However, its perception might extremely differ in various industries. Sustainable CREM practices have been extensively analyzed in recent studies, yet real estate is an ambiguous field and the practices still lack holistic understanding. This research aimed to summarize and systematize the present sustainable CREM practices and propose a generic sustainability maturity model for CREM.Design/methodology/approach – The research process was implemented in accordance with the grounded theory approach. Research data were collected in semi‐structured interviews with major Finnish companies, recognized for their environmental work. The scope of the research was nine interviews.Findings – The result of this research is the generic sustainability maturity model for CREM. It consists of 18 most typical sustainable CREM practices at the companies interviewed. The model demonstrates the value of implementing sustainable CREM.Originality/value – Sustainability maturity model for CREM is an indicative tool for sustainability maturity assessment in CREM. The model demonstrates how CREM contributes to company's sustainability and provides a holistic approach towards the existing sustainable CREM practices. Additional practical implications of the model include sustainable CREM benchmarking and communication with stakeholders.